2017
DOI: 10.5897/jpp2016.0435
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant potential and cytotoxicity of Randia dumetorum Lam. leaf extract

Abstract: The aim of the current study was to explore the antioxidant potential and cytotoxicity of different 'fractions from the leaf extract of Randia dumetorum. Proximate analysis and phytochemical screening were done with standard protocol. The antioxidant activity was evaluated by using reducing power assay, total antioxidant capacity determination, determination of total phenolic content, determination of total flavonoid content and reduction of ferric ions by ortho-phenanthroline color method. In the antioxidant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Brine shrimp lethality assay was done to study the cytotoxic activities of C. spinosa leaf extract and lethal concentration (LC 50 ) was determined. The LC 50 values of water and ethanol extract were 0.94 and 0.23 µ g/ml, respectively [ 12 ]. A similar study was done in the methanolic extract of the stem and the LC 50 value was found to be 1.32 µ g/mL [ 29 ].…”
Section: Toxicological Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Brine shrimp lethality assay was done to study the cytotoxic activities of C. spinosa leaf extract and lethal concentration (LC 50 ) was determined. The LC 50 values of water and ethanol extract were 0.94 and 0.23 µ g/ml, respectively [ 12 ]. A similar study was done in the methanolic extract of the stem and the LC 50 value was found to be 1.32 µ g/mL [ 29 ].…”
Section: Toxicological Aspectsmentioning
confidence: 99%
“…5 m of height, leaves are ovate, simple, shiny, and pubescent [ 8 ], and flowers are white solitary and possess a honey-like fragrance [ 9 ]. This plant has been reported from various parts of India [ 10 ], Nepal, Bangladesh, South China [ 11 ], and the African subcontinent [ 12 ]. C. spinosa is reported to be distributed in tidelands of semitropical and subtropical areas [ 13 ].…”
Section: Introductionmentioning
confidence: 99%